Bases for a public policy on sustainable urban mobility during COVID-19 - Tantaleán Olano, Gladis Mariela; Pérez Azahuanche, Manuel Angel; Vela Meléndez, Lindon; Reynosa Navarro, Enaidy (Revista Venezolana de Gerencia, 2024)
Sustainable urban mobility is essential for the proper functioning of cities, favoring transportation models that consume fewer resources and generate lower environmental costs. In contexts of health emergencies such as the COVID-19 pandemic, it becomes especially relevant by allowing the establishment of the necessary social distancing to break the chain of contagion. The objective of this study was to characterize the current situation of urban mobility in the city of Trujillo, Peru, and establish bases for the design of relevant public policies and interventions during the pandemic. The methodology used was cross-sectional, descriptive, and with a mixed approach, applying surveys to a sample of 384 citizens and in-depth interviews with nine specialists. The data were processed with SPSS-26 and ATLAS.ti v9. As results, it was found that 83.3% of citizens are willing to use bicycles, 87.2% indicate the need to implement bike lanes, and 91.1% highlight that this type of mobility prevents the spread of COVID-19. It is concluded that there is a low preference for sustainable modes of transportation and a high dependence on private motorized transportation in Trujillo prior to the pandemic. However, there is a marked willingness among citizens to use bicycles if proper conditions are enabled, since it is perceived as an effective way to prevent contagion, reduce pollution, promote healthy habits, and facilitate labor accessibility. Therefore, it is suggested that there is an urgent need to formulate public policies aimed at promoting sustainable urban mobility, contemplating cycling infrastructure, awareness campaigns, and regulations that prioritize non-polluting and safe modes of transportation.